Concise Asymmetric Synthesis of Deepoxyalchornoic Acid and (12R,13R)-Isoleukotoxin Diol - Fernandes, Rodney A.; Gorve, Dnyaneshwar A.; Papnai, Himanshu (Synthesis, 2024)
The first asymmetric synthesis and structural confirmation of deepoxyalchornoic acid have been accomplished from commercially available starting materials. Asymmetric dihydroxylation and Wittig olefination has been strategically executed to achieve a concise synthesis of deepoxyalchornoic acid and (12R,13R)-isoleukotoxin diol from a common intermediate chiral γ-lactone.
Keywords: deepoxyalchornoic acid; (12R,13R)-isoleukotoxin diol; lactone; asymmetric dihydroxylation; Wittig olefination; natural product